Stable isotopes of carbon and nitrogen from multiple species of invertebrates, teleosts, elasmobranchs, and marine mammals sampled in Cumberland Sound, 2007-2009 - Fisk, Aaron; McMeans, Bailey (Canadian Cryospheric Information Network, 2012)
Samples of macroaglae (Fucus distichus), several zooplankton species (e.g. Calanus hyperboreus, Sagitta spp.), benthic invertebrates (e.g. scallop Chlamys islandica, snail Buccinum cyaneum, clam Hiatella arctica), teleosts (herring Clupea harengus, capelin Mallotus villosus, char Salvelinus alpines, sculpin Myoxocephalus scorpioides (adults and larvae), turbot Reinhardtius hippoglossoides), two elasmobranchs (arctic skate Amblyraja hyperborea, Greenland shark Somniosus microcephalus), two pinnipeds (harp seal Pagophilus groenlandicus, ringed seal Pusa hispida) and two cetacean (beluga whale Delphinapterus leucas , narwhal Monodon monoceros) species were collected from Cumberland Sound (Nunavut). Zooplankton were sampled by surface horizontal tows and vertical hauls using a plankton net. Benthic invertebrates were sampled by ponar or dip net, herring, char and sculpin by gillnet, capelin by dip net and turbot, arctic skate and Greenland sharks by bottom long line. Marine mammals were sampled during Inuit subsistence hunts. Stable isotopes of nitrogen and carbon were analyzed from freeze dried, homogenized and lipid extracted (using 2:1 chloroform:methanol) whole zooplankton, soft tissues of benthic molluscs, and muscle tissues of fish, elasmobranchs and marine mammals. Following pre-treatment (i.e. lipid extraction), approximately 0.5 mg of each sample was weighed into tin capsules and run on a continuous-flow isotope ratio mass spectrometer (Delta V Advantage, Thermo Electron). Replicate analyses of NIST (National Institute of Standards and Technology) standard bovine muscle (NIST 8414, N = 70) and internal lab standard (tilapia muscle, N = 7) yielded a precision (i.e. one standard deviation) of 0.14 and 0.25 per mil. for delta 15N and 0.07 and 0.10 per mil. for delta 13C, respectively. Samples were collected during both summer/open water (early August) and late winter/ice cover (early April) to explore seasonal changes in species' stable isotopes and overall shifts in food web structure. : Purpose: As the largest fish and most prolific eater in the Arctic seas, the Greenland shark is a very unique vertebrate in the Arctic ecosystem. Given their diet, Greenland sharks hold a position in the food web similar to that of polar bears. Little is known about how these sharks behave or how their behaviour might shift in response to changes in climate. Given their importance in the Arctic food web, this project is assessing the feeding ecology and behaviour of the Greenland shark under different ice conditions to determine how different environments affect this fish. This assessment involves the analysis of stable isotopes of carbon and nitrogen from multiple species of invertebrates, teleosts, elasmobranchs, and marine mammals sampled in Cumberland Sound in 2007, 2008 and 2009. : Summary: Not Applicable